Penerapan Sanksi Denda Tilang Elektronik Traffic Law Enforcement (E-TLE): Berdasarkan Undang-Undang No. 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Anjar Rudi Admoko; Supriyadi Supriyadi (Postgraduate University of Merdeka Malang, 2022)
This study aims to examine several things, namely the imposition of fines and obstacles in the application of Electronic Traffic Law Enforcement (E-TLE) fines in the Sura-baya City area and solutions in overcoming obstacles in the application of Electronic Traffic Law Enforce-ment (E-TLE) tickets to traffic violators in the Surabaya City area. The type of research used is the legal research method. The results showed that the application of E-tickets, the application of fines for electronic traffic law enforcement (E-TLE) tickets went smoothly. The number of violations encountered in the field during the process is motorcycle drivers not wearing helmets, violating markings, and violating speed limits. The solutions carried out in overcoming the obstacles that occur during the implementation of the electronic ticketing system are: a) Increase the number of CCTV installations on a number of roads in Surabaya City, b) Expand the socialization of electronic ticketing, and c) Reduce the name transfer fee.DOI: https://doi.org/10.26905/mlj.v3i2.9220